Sosialisasi Penggunaan Teknologi QRIS untuk Meningkatkan Transaksi Nontunai pada UMKM - Dynne Andriany; Diar Muzna Tangke; Hedi Musriha (Jurnal Nusantara Berbakti, 2025)
The use of technology in economic transactions is increasing, one of which is the digital payment system known as the Quick Response Code Indonesian Standard (QRIS). MSME players are not affected by the development of the QRIS digital payment system. However, currently not all MSMEs, especially micro businesses, have knowledge about this. Considering this phenomenon, this service activity was carried out with the aim of providing knowledge about the benefits and working procedures of QRIS in encouraging the efficiency of payment transactions. One of the micro businesses in Ambon city that has not yet used QRIS is Es Kelapa NTB. This business has quite a lot of loyal consumers but has not utilized QRIS technology, which causes a lack of knowledge about QRIS. The method of this activity begins with target identification, socialization about QRIS and monitoring and evaluation. Activities were carried out smoothly, every question about QRIS was answered in detail so as to provide knowledge and understanding of the digital payment system. It is hoped that this activity can make business actors have confidence in the security and convenience that can be provided by the QRIS digital payment system.